The Canadian dollar, 1948-1962 - Wonnacott, Paul. (Toronto : University of Toronto Press, 1965)
This book consists of two substantially independent parts. Part I was published as The Canadian Dollar 1948-1958 and was reviewed in this journal (September 1962, 52, 874-75). The present review is restricted to Part II, which discusses the events and policies from 1958 until 1962 when the Canadian government abandoned the system of flexible foreign exchange rates. The study also includes description and commentary on other more specific policies. Policies to reduce foreign control of Canadian industry which affected the composition and the volume of capital inflows.
"Incorporates, as Part One, [the author's] The Canadian dollar, 1948-1958."
Includes bibliographic references
usc 20/07/18
Loans
Keywords: Foreign exchange; Monetary policy; Canada